Intensity‐modulated radiation therapy as primary treatment for oropharyngeal squamous cell carcinoma. Issue 12 (6th March 2013) - May, James T.; Rao, Nikhil; Sabater, Roberto D.; Boutrid, Hinda; Caudell, Jimmy J.; Merchant, Faisal; Han, Gang; Padhya, Tapan A.; McCaffrey, Judith C.; Tanvetyanon, Tawee; Deconti, Ronald; Kish, Julie; et al.
<x xml:space="preserve">Abstract</x> Background Over the past decade, intensity‐modulated radiation therapy (IMRT) has gained widespread use in the treatment of head and neck cancer. Methods All patients with squamous cell carcinoma of the oropharynx treated with primary IMRT with or without chemotherapy over a 5‐year period were reviewed. Outcomes and morbidity were analyzed and compared with previously published data. Results In all, 170 patients were included in the analysis. The 3‐year local control, locoregional control, disease‐free survival, and overall survival rates were 92%, 91%, 80%, and 87%, respectively. Feeding tubes were present in 55% of patients during treatment, but remained in only 1% 2 years following treatment. Conclusions This study confirms that IMRT yields excellent treatment outcomes for oropharyngeal carcinoma. Although acute toxicity remains a problem, late toxicity rates are low and long‐term feeding tube dependence is rare compared with conventional radiation therapy. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1796–1800, 2013